An application of a tent map initiated Chaotic Firefly algorithm for optimal overcurrent relay coordination - Gokhale, S.S.; Kale, V.S. (International journal of electrical power & energy systems, 2016)
•Firefly algorithm is efficient to coordinate over current relays.•Chaotic Firefly algorithm using tent maps is superior to the Firefly algorithm.•Initialization of random factor alpha near unity gives the best results.•Chaotic number generation is better than randomly generated numbers for relay coordination. Over-current relays provide primary as well as backup protection to electrical distribution systems. These relays should be coordinated and set at the optimum values, to minimize the total operating time and hence ensure that least damage is caused when a fault occurs. While they provide backup protection, it is also imperative to ensure that their settings should not cause their inadvertent operation and subsequent sympathy trips. This paper describes a Chaotic Firefly algorithm (CFA) for optimal time coordination of these relays. The algorithm has been implemented in MATLAB and tested on several systems, out of which two have been illustrated in this paper. The results obtained by the Chaotic Firefly algorithm are compared with those obtained by the conventional Firefly algorithm (FA). The novel feature of this paper is the application of the Chaotic Firefly algorithm to the problem of over-current relay coordination.